Managing thrombosis and cardiovascular complications of COVID-19: answering the questions in COVID-19-associated coagulopathy. (3rd August 2021) - Iba, Toshiaki; Levy, Jerrold H.; Connors, Jean Marie; Warkentin, Theodore E.; Thachil, Jecko; Levi, Marcel
ABSTRACT: Introduction: The first patients with Coronavirus disease 2019 (COVID-19) emerged at the end of 2019. This novel viral infection demonstrated unique features that include prothrombotic clinical presentations. However, one year after the first occurrence, there remain many unanswered questions. We tried to address some of the important queries in this review. Areas covered: We raised the following critical questions. 'Why is COVID-19 so hypercoagulable?', 'Why are most coagulation test results relatively normal?', 'Why is COVID-19-associated coagulopathy more thrombotic than most other infectious diseases?', 'Why is arterial thrombus formed frequently?', 'Is anticoagulant therapy for COVID-19 effective?', and 'Are there racial disparities in thrombosis in COVID-19?' Expert opinion: There are commonalities and differences in the pathogeneses and clinical features between COVID-19 and other infectious diseases. Correct understanding will help discussing appropriate anticoagulation prophylaxis or treatment for thromboembolism.